Annulment of Marriage and Separation in Wigry and Augustów or Sejny Diocese - JEMIELITY, WITOLD (Prawo Kanoniczne, 2012)
Civil marriages and divorces were not known in the early ages of Poland. This situation has changed considerably in this respect after the partitions of the country. The area of the Wigry Diocese (1799-1807) and Augustów or Sejny Diocese (1818-1925) were in the Prussian part (1795-1807) in the Grand Duchy of Warsaw (1807-1815) and in the Congress Kingdom of Poland. Each government had its own marriage law, while the Church pushed for following the catholic norms regarding the sacrament of matrimony. Napoleon’s Code, introduced on the base of the decree on this 20th January, 1808, ordered contraction of civil marriages and allowed to get divorced. The Congress Kingdom of Poland that was erected on the Vienna Congress in the year 1815, inherited the legal status of the Grand Duchy Warsaw. The law concerning marriages introduced in the year 1836 mitigated the binding regulation to certain degree. First of all, marriages was acknowledged to be a religious institution, and then, in the second place, an institution of the civil law. The Sejny Church Court investigated questions concerning annulment of marriages due to such reasons as: secrecy, compulsion, physical disability of a woman, impotence of a man polygamy. Most cases concerned separation from bed and board. The judgments were issued in Latin. The Church Court gave long-drawn-out explanations of the decisions alleged testimonies of the parties concerned and witnesses, quoted the Church Law, and, after the year 1836, the proper article of the Law concerning marriages.